2016
DOI: 10.1016/j.rasd.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

‘I am who I am’: Reputation concerns in adolescents on the autism spectrum

Abstract: Background: Adolescence is often characterised by an increased concern for one's reputation in typical development. The extent to which autistic adolescents are concerned for their reputation, however, is unclear.Method: Semi-structured interviews were conducted with 12 autistic adolescents and five members of school staff to examine reputation concerns in autism. Topics discussed included being 'cool', friendships, worries and self-concepts.Results: Thematic analysis revealed that autistic adolescents were so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 56 publications
7
28
0
Order By: Relevance
“…By doing so, he also expresses that honesty is in many ways a choice, specifically a choice to stay true to his inner code of conduct rather than achieving transient popularity. This ties with research examining reputation management in autistic adolescents, who are less concerned with "being cool" and more interested in being true to themselves (Cage, Bird, & Pellicano, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…By doing so, he also expresses that honesty is in many ways a choice, specifically a choice to stay true to his inner code of conduct rather than achieving transient popularity. This ties with research examining reputation management in autistic adolescents, who are less concerned with "being cool" and more interested in being true to themselves (Cage, Bird, & Pellicano, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…Our findings present further evidence for potential social capacity in autism. Future research should examine the development of this capacity in adolescence, especially since qualitative evidence suggests that autistic adolescents can be concerned about their reputation (Cage et al 2016) and adolescence appears to be a pertinent time for reputation concerns in typical individuals (Blakemore and Mills 2014). Finally, although the current study did not find gender differences within any of the tasks, future research would benefit from a larger female sample to test for any potential gender differences, particularly given the suggestion that autistic girls may be better at “camouflaging” or “masking” (Head et al 2014) and therefore cognizant of how others’ might perceive them.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown, however, that reputation management is possible in some adolescents and adults on the autism spectrum (Cage et al 2013, 2016; Scheeren et al 2015), which raises questions about the underlying abilities that might explain variability in explicit and implicit reputation management in autistic individuals. Two main hypotheses have been proposed to explain why autistic individuals have difficulties with reputation management.…”
Section: Individual Differences In Reputation Managementmentioning
confidence: 99%
“…Qualitative methods can provide a deeper understanding of friendship in ASD from the perspective of adolescents with ASD themselves [ 32 33 ], and highlight the roles that anxiety and loneliness play in developing and maintaining friendship in the daily encounters of adolescents with ASD. Qualitative methods can also empower voices of adolescents with ASD, who often go unheard in autism research [ 34 ].…”
Section: Introductionmentioning
confidence: 99%